Proton acceleration and high energy density physics from laser foil interactions - Norreys, P; Beg, F; Clark, E; Tatarakis, M; Zepf, M; Dangor, A; Wei, M; Krushelnick, K (2005)
Our team has provided the first observations of energetic ion beam production from the front and rear surfaces thin foil targets upon irradiation by an intense laser beam in the relativistic regime. We invented a new plasma diagnostic technique in which "layered" track detectors and dosimetry media were used to simultaneously record ion angular emission patterns as well as ion spectral information. These results have led to a large number of further experiments in which similar measurement techniques were used and in which protons have been measured up to 58 MeV. The source and acceleration mechanisms for these proton beams have been extensively investigated. There have also been a number of proposed applications for these ion beams, such as for injectors into subsequent conventional acceleration stages, for probing of dense plasmas and for inertial confinement fusion experiments. © 2005 IEEE.